2015
DOI: 10.1111/cge.12625
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis type 1 and malignancy in childhood

Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant hereditary neurocutaneous syndrome characterized by multi-system involvement and an increased incidence of both benign and malignant tumors. In this study, we evaluated the clinical presentation and prognosis of NF1 and malignancy. Between 1975 and 2013, 26 (5%) of the 473 patients with NF1 at our center developed non-neurofibroma neoplasms. The patient files of 26 subjects with tumors, other than optic glioma, were analyzed retrospectively to evaluate cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 25 publications
0
41
1
2
Order By: Relevance
“…The association of other embryonic tumours and NF1 is also under debate. Varan et al (75) report two neuroblastoma cases in their cohort of NF1 patients. It is important to keep in mind that also neuroblastoma (86) and Wilms' tumour (81,82) have been diagnosed in CMMRD patients.…”
Section: Potential Impact Of Cmmrd On Our Current Knowledge Of Nf1-asmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of other embryonic tumours and NF1 is also under debate. Varan et al (75) report two neuroblastoma cases in their cohort of NF1 patients. It is important to keep in mind that also neuroblastoma (86) and Wilms' tumour (81,82) have been diagnosed in CMMRD patients.…”
Section: Potential Impact Of Cmmrd On Our Current Knowledge Of Nf1-asmentioning
confidence: 99%
“…NF1-associated pilocytic astrocytomas and OPG have a particularly benign behaviour and hardly ever develop into life-threatening disease (10,68,69). There are, however, also a few case reports (70-72) and retrospective clinical-pathological studies (73)(74)(75) that report a possible association of childhood high-grade (WHO III or IV) CNS tumours and NF1. Huttner et al (73) searched for patients who had a childhood glioblastoma and fulfilled NIH clinical criteria of NF1 using a computerized search engine of the medical records of patients from a single institution and found five patients fulfilling these criteria.…”
Section: Potential Impact Of Cmmrd On Our Current Knowledge Of Nf1-asmentioning
confidence: 99%
“…Analyses of 9,432 long-term neuroblastoma survivors in 3 major studies indicated that 96 patients developed second cancers, including carcinomas, soft tissue sarcomas, glioblastomas, meningioma, melanomas, and hematologic malignancies, but none developed medulloblastoma (Table 3). [5][6][7] Neuroblastoma and, less commonly, medulloblastoma, have been reported in patients with cancer predisposition syn- [22][23][24] Our patient did not have clinical stigmata of these conditions and her genetic testing was negative for these syndromes.…”
Section: Discussionmentioning
confidence: 63%
“…Early diagnosis of NF-1 in the pediatric population is crucial, since there is an association between von Recklinghausen disease and malignant tumors such as gliomas, leukemias, melanomas, and non-Hodgkin lymphomas [15]. Additionally, when associated with NF-1, PNs have the potential of undergoing malignant sarcomatous transformation, adding considerably to overall morbidity and mortality [15]. Thus, excluding malignancy of an aggressively growing plexiform lesion, the NF-1 diagnosis additionally justified immediate resection.…”
Section: Discussionmentioning
confidence: 99%